Metacognitive Therapy for Depression in Adults: A Waiting List Randomized Controlled Trial with Six Months Follow-Up - Hagen, Roger; Hjemdal, Odin; Solem, Stian; Kennair, Leif Edward Ottesen; Nordahl, Hans M.; Fisher, Peter; Wells, Adrian (Frontiers in Psychology, 2017)
This randomized controlled trial examines the efficacy of metacognitive therapy (MCT) for depression. Thirty-nine patients with depression were randomly assigned to immediate MCT (10 sessions) or a 10-week wait list period (WL). The WL-group received 10 sessions of MCT after the waiting period. Two participants dropped out from WL and none dropped out of immediate MCT treatment. Participants receiving MCT improved significantly more than the WL group. Large controlled effect sizes were observed for both depressive (d = 2.51) and anxious symptoms (d = 1.92). Approximately 70-80% could be classified as recovered at post-treatment and 6 months follow-up following immediate MCT, whilst 5% of the WL patients recovered during the waiting period. The results suggest that MCT is a promising treatment for depression. Future controlled studies should compare MCT with other active treatments.